2021
DOI: 10.1037/pag0000566
|View full text |Cite
|
Sign up to set email alerts
|

Subjective age and informant-rated cognition and function: A prospective study.

Abstract: The present study examined whether subjective age is related to informant-rated cognition. Participants were adults (N ϭ 2,337, mean age ϭ 69.84 years, SD ϭ 7.45) from the Health and Retirement Study who provided subjective age and demographic factors in 2008/2010 and informant-rated cognition in 2016 as part of the Harmonized Cognitive Assessment Protocol. An older subjective age was associated with informant reports of steeper cognitive decline, worse cognitive function, lower ability, and loss of ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The fact that more negative generalized and personal aspects of VoA associated with more SCC is consistent with previous studies that reported an association between older subjective age (Hülür et al, 2015;SegelÀKarpas & Palgi, 2019;Siebert et al, 2020;Stephan et al, 2020) and worse subjective cognition. These associations between VoA and more SCC can be explained at least partially by the age stereotype embodiment theory (Levy, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The fact that more negative generalized and personal aspects of VoA associated with more SCC is consistent with previous studies that reported an association between older subjective age (Hülür et al, 2015;SegelÀKarpas & Palgi, 2019;Siebert et al, 2020;Stephan et al, 2020) and worse subjective cognition. These associations between VoA and more SCC can be explained at least partially by the age stereotype embodiment theory (Levy, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Both categories of VoA have been shown to have long-term effects on health, including cognitive, psychological, and physical health outcomes (for review, see Wurm et al, 2017). Few studies have investigated how VoA relate to SCC, and the studies that have looked at this association have examined the measure of subjective age specifically (Hülür et al, 2015; Segel-Karpas & Palgi, 2019; Stephan et al, 2020; for an exception, see Siebert et al, 2020). However, given the abovementioned studies, it stands to reason that various other indicators of VoA (encompassing both generalized and personal VoA, see below) may influence a person’s perceived cognitive abilities, and may do so more powerfully in older age groups.…”
mentioning
confidence: 99%
“…Other age assessments are often used to provide a more complete understanding of an individual’s age identity and their general attitudes toward aging (Diehl et al, 2014, 2021), as well as their aging ideals and desires (e.g., Galambos et al, 2003). For example, subjective age (or felt age) indicates the age a person feels most of the time (e.g., Barak, 1987; Kaufman & Elder, 2002; Kotter-Grühn et al, 2016), which can differ dramatically from their chronological age (e.g., Galambos et al, 2005; Geraci et al, 2018; Karaca et al, 2024; Kornadt et al, 2021; Li et al, 2021; Pinquart & Wahl, 2021; Stephan et al, 2021; Wettstein et al, 2023).…”
mentioning
confidence: 99%